Nlrp3 is a key modulator of diet-induced nephropathy and renal cholesterol accumulation - Bakker, Pieter J.; Butter, Loes M.; Kors, Lotte; Teske, Gwendoline J.D.; Aten, Jan; Sutterwala, Fayyaz S.; Florquin, Sandrine; Leemans, Jaklien C. (Kidney international, 2014)
Metabolic syndrome (MetSyn) is a major health concern and associates with the development of kidney disease. The mechanisms linking MetSyn to renal disease have not been fully elucidated but are known to involve hyperuricemia, inflammation, and fibrosis. Since the innate immune receptor Nlrp3 is an important mediator of obesity and inflammation, we sought to determine whether Nlrp3 is involved in the development of MetSyn-associated nephropathy by giving wild-type or Nlrp3-knockout mice a Western-style compared to a normal diet or water without or with fructose. A plausible driver of pathology, the Nlrp3-dependent cytokine IL-1β was not increased in the kidney. Interestingly, Nlrp3-dependent renal cholesterol accumulation, another well-known driver of renal pathology, was enhanced during MetSyn. We also determined the role of Nlrp3 and fructose-fortified water on the development of MetSyn and kidney function since fructose is an important driver of obesity and kidney disease. Surprisingly, fructose did not induce MetSyn but, irrespective of this, did induce Nlrp3-dependent renal inflammation. The presence of Nlrp3 was crucial for the development of Western-style diet–induced renal pathology as reflected by the prevention of renal inflammation, fibrosis, steatosis, microalbuminuria, and hyperuricemia in the Nlrp3-knockout mice. Thus, Nlrp3 may mediate renal pathology in the context of diet-induced MetSyn.